ENVIRONMENTAL MIGRATION POLICY IN CANADA Lessons from Australia, New Zealand, and beyond - Brown, Taylor (Université d'Ottawa | University of Ottawa, 2022)
Canada has not done enough to address environmental migration policy development in the face of climate change. First, I use moral, economic, and political arguments to explain why Canada should develop an environmental migration policy. Second, I analyze lessons Canada can take away from Australia, New Zealand, and a few international frameworks on developing such a policy. As for moral considerations, Canada is a large, wealthy, and stable nation that has relied on Greenhouse Gas (GHG) emitting industries (Kaduuli, 2021). Canada is also a signatory to multiple climate change and migration initiatives and has been historically receptive to migrants (Government of Canada, 2021a; Friedrich, Ge & Pickens, 2020). Economically, Canada’s labour market could benefit from an expansion of the Refugee Act to include environmental migrants as studies show refugees perform well in the Canadian market and contribute to the Canadian economy, while climate change adaptation and mitigation costs continue to increase (UNHCR Canada, 2019; Arora, 2014; Dupraz-Dobias, 2020). As for political motivation, Canada may be pressured by the U.S. and the broader international community to accept environmental migrants as the number of migrants fleeing Latin America and the Caribbean due to unliveable environmental conditions increases (Tower, 2021; Immigration and Refugee Board Canada, 2018). Canadian policymakers have many options to approach environmental migration policy development, including Australia’s conservative-restrictive approach, New Zealand’s open-liberal approach, or an amalgamation of both. However, I argue that findings show more benefits to a progressive approach to migrant policy. The Canadian state should also consider using international policies to develop a framework with well-thought input from around the globe. These frameworks argue that environmental migration policies should be developed with respect for human rights, migrant inclusion, and long-term planning and preparation for environmental migrants. Including international counsel within an environmental migration policy could help policymakers address more potential migrant risks and reduce harm. It is time for Canada to develop an environmental migration policy, and to make it effective and efficient, policymakers must look abroad to Australia, New Zealand and beyond. Key Words Environmental migration, refugee, immigration policy, climate change, Canada, Australia, New Zealand